Einstein's quantum riddle [videorecording (DVD)] - Lochhead, Jamie; Lochhead, Jamie; Meyers, Eric, 1959- ([publisher not identified], 2019)
Albert Einstein proposes his theory of quantum entanglement in an effort to disprove quantum mechanics.